ЗАЗОРОТ И ДИСЛОКАЦИЈАТА ВО ДРАМСКИТЕ ТЕКСТОВИ КАЗАБАЛКАН, ЕВРОАЛИЕН И ХОТЕЛ ЕВРОПА ОД ГОРАН СТЕФАНОВСКИ (Philological Studies, 2019)
GORAN STEFANOVSKI In her book on the subject of abjection, The Powers of Horror, the French theorist Julia Kristeva links the abject/abjection with the loss of the distinction between self and other. This text examines the relation between abjection and dislocation in several plays by Goran Stefanovski.
Keywords: Goran Stefanovski, Julia Kristeva, abject, abjection, dislocation, loss, homeland, language, identity, culture